Scientific Potential as the Basis of Innovation Development of Kazakhstan - Yessengeldin, Bauyrzhan; Sitenko, Diana; Murzatayeva, Gulnaz; Yessengeldina, Anar (International Journal of Economics and Financial Issues, 2016)
The article describes the development of market mechanisms of high-tech sector of innovation system of the Republic of Kazakhstan. The structure of domestic expenditure on research and development of different countries is analyzed. The article revealed that the main problem for Kazakhstan science is the low level of development of innovation system, i.e., research and development are still not getting the production application. The results of the research activities and the estimation of the impact of research are considered. The relationship between the structure of domestic expenditure on research and development and the number of patent applications was investigated. Positive correlation between the number of patent applications and the financing of science business sector was revealed. Keywords: innovation, science, research JEL Classifications: N15, O32